2017
DOI: 10.1167/iovs.16-21283
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Placenta Growth Factor Reduces Subretinal Mononuclear Phagocyte Accumulation in Choroidal Neovascularization

Abstract: The results hint at an interplay between PlGF/VEGFR1 and MPs that is important in the early phase of CNV. A combined inhibition of VEGF-A and PlGF is superior to a specific anti-PlGF treatment in terms of subretinal MP recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 48 publications
7
21
1
1
Order By: Relevance
“…These results are in accordance with a recent report comparing antibody-mediated PGF inhibition with aflibercept at a later time point (14 days) after laser treatment [17]. In that paper, Crespo-Garcia et al identified higher PGF and VEGF levels in the laser-damaged retina using immunostainings [17]. Here, we significantly expand these findings by showing in situ co-expression of PGF and VEGF by Iba1-positive mononuclear phagocytes in the RPE/choroid complex.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in accordance with a recent report comparing antibody-mediated PGF inhibition with aflibercept at a later time point (14 days) after laser treatment [17]. In that paper, Crespo-Garcia et al identified higher PGF and VEGF levels in the laser-damaged retina using immunostainings [17]. Here, we significantly expand these findings by showing in situ co-expression of PGF and VEGF by Iba1-positive mononuclear phagocytes in the RPE/choroid complex.…”
Section: Discussionsupporting
confidence: 93%
“…Our data show that the PGF inhibition, especially with aflibercept, dampens vascular leakage and CNV 7 days after laser application. These results are in accordance with a recent report comparing antibody-mediated PGF inhibition with aflibercept at a later time point (14 days) after laser treatment [17]. In that paper, Crespo-Garcia et al identified higher PGF and VEGF levels in the laser-damaged retina using immunostainings [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Dennoch ist den Autoren hier ein Einblick in die entzündlichen Vorgänge in der Netzhaut von AMD-Patienten gelungen. Die Daten zur Absenkung des VEGF-A nach Anti-VEGF-A-Behandlung sowie die erhöhten Spiegel an MCP1 bei AMD-Patienten decken sich gut mit den Daten anderer Publikationen [2,3], was belegt, dass die von Motohashi erhobenen Daten aussagekräftig sind. Die Absenkung der inflammatorischen Faktoren nach Aflibercept könnte mit tierexperimentellen Daten korrelieren, in denen gezeigt wurde, das eine Aflibercept-Anwendung bei der Laser-induzierten chorioidalen Neovaskularisation (CNV) die Aktivierung von mononukleären Makrophagen wie Mikroglia hemmen kann.…”
Section: Transfer In Die Praxis Von Prof Dr Olaf Strauß (Berlin)unclassified